2009
DOI: 10.1152/ajprenal.90411.2008
|View full text |Cite
|
Sign up to set email alerts
|

Transepithelial fluxes of adenosine and 2′-deoxyadenosine across human renal proximal tubule cells: roles of nucleoside transporters hENT1, hENT2, and hCNT3

Abstract: Elwi AN, Damaraju VL, Kuzma ML, Mowles DA, Baldwin SA, Young JD, Sawyer MB, Cass CE. Transepithelial fluxes of adenosine and 2Ј-deoxyadenosine across human renal proximal tubule cells: roles of nucleoside transporters hENT1, hENT2, and hCNT3. Am J Physiol Renal Physiol 296: F1439 -F1451, 2009. First published March 18, 2009 doi:10.1152/ajprenal.90411.2008.-This study examined the roles of human nucleoside transporters (hNTs) in mediating transepithelial fluxes of adenosine, 2Ј-deoxyadenosine, and three purine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 53 publications
2
16
1
Order By: Relevance
“…Proximal tubular epithelial cells generally have lower TEER consistent with a looser epithelium while distal tubular epithelial cells have higher TEER corresponding to a tighter epithelium. The steady state resistance of ∼100 Ω-cm 2 is consistent with other cultured renal tubular epithelial cells of proximal tubule origin (Wieser et al , 2008 and Elwi et al , 2009). To evaluate the barrier function, inulin leak was measured.…”
Section: Resultssupporting
confidence: 86%
“…Proximal tubular epithelial cells generally have lower TEER consistent with a looser epithelium while distal tubular epithelial cells have higher TEER corresponding to a tighter epithelium. The steady state resistance of ∼100 Ω-cm 2 is consistent with other cultured renal tubular epithelial cells of proximal tubule origin (Wieser et al , 2008 and Elwi et al , 2009). To evaluate the barrier function, inulin leak was measured.…”
Section: Resultssupporting
confidence: 86%
“…Similar to recent studies of human kidney proximal tubule cells [108], ENTs are found on both the luminal and abluminal surfaces of BBB endothelial cells and on the basolateral and apical surfaces of BCSFB epithelial cells, whereas CNTs are exclusively expressed in abluminal and apical membranes, respectively. This vectorial distribution of NTs in BBB and BCSFB cells is mirrored by the asymmetric distribution of OCT, OAT and MRP transporters [109].…”
Section: Nts Of the Blood-brain Barrier And Choroid Plexussupporting
confidence: 85%
“…Single nucleotide polymorphisms involved in the metabolic pathway of nucleoside analogues have been identified and are postulated to influence drug exposure [4447]. ENT1, ENT2, and concentrative nucleoside transporter 3 have been shown to influence in vitro distribution and accumulation of fludarabine [3,4,6]. These transporters are expressed in both target tissues and renal epithelial cells of the kidney and may impact drug exposure and disposition through several mechanisms [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Administered intravenously as a prodrug, fludarabine monophosphate (f-ara-AMP) undergoes rapid dephosphorylation in the plasma to the systemically circulating compound, f-ara-a. F-ara-a is then transported from the plasma into cells by several uptake transporters, including equilibrative nucleoside transporters (ENT1, ENT2) and the concentrative nucleoside transporters 3 [36]. In the cytoplasm, f-ara-a is sequentially phosphorylated to the active triphosphate species (f-ara-ATP), which inhibits DNA synthesis and RNA production, inducing apoptosis [1,2,7].…”
Section: Introductionmentioning
confidence: 99%